Recognition of Multiscale Dense Gel Filament-Droplet Field in Digital Holography With Mo-U-Net - Pang, Zhentao; Zhang, Hang; Wang, Yu; Zhang, Letian; Wu, Yingchun; Wu, Xuecheng (Frontiers in Physics, 2021)
Accurate particle detection is a common challenge in particle ﬁeld characterization with digital holography, especially for gel secondary breakup with dense complex particles and filaments of multi-scale and strong background noises. This study proposes a deep learning method called Mo-U-net which is adopted from the combination of U-net and Mobilenetv2, and its application to segment the dense filament-droplet field of gel drop. Specially, a pruning method is applied on the Mo-U-net, which cuts off most of its deep layers to save its training time while remaining a high segmentation accuracy. The performances of the segmentation are quantitatively evaluated by three indices, the positive intersection over union (PIOU), the average square symmetric boundary distance (ASBD) and the diameter-based prediction statistics (DBPS). The experimental results show that the area prediction accuracy (PIOU) of Mo-U-net reaches 83.3%, which is about 5% higher than that of adaptive-threshold method (ATM). The boundary prediction error (ASBD) of Mo-U-net is only about one pixel-wise length, which is one third of that of ATM. And Mo-U-net also shares a coherent size distribution (DBPS) prediction of droplet diameters with the reality. These results demonstrate the high accuracy of Mo-U-net in dense filament-droplet field recognition and its capability of providing better statistical data in a variety of holographic particle diagnostics.